Tawhidic epistemology and the affirmation of oneness: understanding the notions of Aḥad, Waḥid, and Tawḥid - Rahman, Shukran Abdul; Hassan, Haslina (Mission Soft Foundation, 2025)
This article examines two Qur’anic concepts, namely Aḥad and Wāḥid, linking them to the concept of Tawḥīd, and their epistemological implications for understanding the foundation of knowledge. It explains how these concepts shape Tawhidic Epistemology (TE), the worldview foundational to intellectual integration in Islamic scholarship. The framework presented is expected to support the broader discourses on the integration of knowledge, aligning with IIUM’s educational philosophy, which emphasizes unity, coherence, and holistic understanding.